Exploring the impact of childhood maltreatment and BPD on impulsivity in crimes of passion - Jin, Michelle; Wang, Zhongrui; Zhou, Ying; Zhong, Jie (Frontiers in Psychiatry, 2023)
Background: Crimes of passion have received widespread attention in recent years. A crime of passion is defined as unpremeditated impulsive aggressive violence. Impulsivity is one of the important aspects leading to a crime of passion. However, impulsivity not only plays a major role in crimes of passion, but is a common feature of many health conditions, including borderline personality disorder (BPD). According to previous studies, one of the important leading factors of BPD is childhood maltreatment, which is also closely related to impulsivity. Although previous studies have confirmed that impulsivity is closely related to childhood maltreatment, BPD, and criminal behavior, few studies have explored the relationship between them and the offenders of crimes of passion. In this study, we explored the relationship between childhood maltreatment, BPD, and impulsivity in crimes of passion and analyzed the impact of the former on the latter. Method: We screened out 133 crimes of passion offenders and 149 other offenders from the Shenzhen male prison in China. All 282 participants then completed The Abbreviated Version of The Barratt Impulsiveness Scale (ABIS), The UPPS (Urgency, Premeditation, Perseverance, Sensation Seeking) Impulsivity Scale, The Mclean Screening Instrument for Borderline Personality Disorder (MSI-BPD), and The Childhood Trauma Questionnaire (CTQ). Results: The results showed that (1) Crimes of passion offenders scored significantly higher in emotional neglect and physical neglect and childhood maltreatment was also significantly higher in the high BPD trait group. (2) Meanwhile, crimes of passion offenders showed significantly higher impulsivity compared to other offenders in attention and nonplanning scales, and impulsivity scores were also significantly higher in the high BPD trait group across all scales. (3) In addition, emotional neglect was found to have a significant impact on the urgency scale in crimes of passion offenders; at the same time, an interaction between physical abuse and high BPD trait was found, which caused impulsivity to increase in crimes of passion offenders. Conclusion: The present study proved the predictive roles of childhood maltreatment and BPD on impulsivity in crimes of passion offenders.